Long-term neurological outcomes of severe traumatic brain injury in the intensive care unit - Kołodziejczyk, Bartłomiej; Damps, Maria; Żmudka, Karol; Mandera, Marek (Frontiers in Pediatrics, 2025)
Severe traumatic brain injury (TBI) remains the leading cause of acquired disability in previously healthy children, with outcomes varying widely despite advanced care. Posttraumatic brain damage may prevent proper functioning despite the implementation of advanced intensive care techniques or early neurosurgical interventions. This retrospective cohort study examined the relationship between specific intensive care unit (ICU) interventions and functional outcomes in 69 pediatric patients with severe TBI treated at the Upper Silesian Children's Health Center in Katowice from 2019 to 2024. Data collected included demographics, injury severity, treatment modalities, and intervention procedures. Long-term neurological outcomes were assessed using the Glasgow Outcome Scale (GOS) via parental interviews. The survival rate was 85.5% (59/69), with a median ICU stay of 8 days [interquartile range (IQR) = 5–11]. Of note, the survival rate was significantly longer in boys (8 days, IQR = 6–12.25) than girls (6 days, IQR = 3–9) (p = 0.021). Almost all patients (97.1%) required sedation upon admission, with a median mechanical ventilation duration of 6 days (IQR = 4–8). This was also longer among boys (7 days, IQR = 4–9.25) than girls (5 days, IQR = 2–7) (p = 0.032). Poorer neurological outcomes (lower GOS scores) were significantly associated with longer ventilation duration (p < 0.001), vasopressor administration (p = 0.002), transfusion of red blood cells (red blood cell, p < 0.001), and transfusion of frozen plasma (fresh frozen plasma, p = 0.009). The intubation site did not significantly affect GOS scores (p = 0.659). Our findings suggest that pediatric TBI patients requiring prolonged ventilatory support, hemodynamic stabilization, and blood product administration face an increased risk of unfavorable outcomes, highlighting the need for early transfer to specialized pediatric trauma centers to optimize recovery potential. Early referral and access to specialized centers can enhance recovery and improve long-term neurological outcomes.